1988
DOI: 10.3354/meps047185
|View full text |Cite
|
Sign up to set email alerts
|

Effects of four organic pollutants on the growth of natural marine bacterioplankton populations

Abstract: Acute and long-term toxicities of 2 low molecular weight polycyclic aromatic hydrocarbons (PAHs) and 2 organochlorine pesticides on bacterial growth were assessed, using incorporation of tritiated thymidine (13H]TdR) into bacterial cell macromolecules as growth indicator of natural populations of coastal bacterioplankton. Acute toxicity of the 4 compounds increased in the following order: naphthalene < phenanthrene < Kepone = pentachlorophenol (PCP), the minimum significantly inhibiting concentrations (p < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…Thus, changes in environmental conditions transform the microbial activities, thereby conferring significant impact to the ecosystem (Choi et al 2002). In fact, marine bacteria's response to the addition of inhibitory substances, organic pollutants and heat has been studied elsewhere (Cole et al 1988;Hudak and Fuhrman 1988;White et al 1991;Shiah and Ducklow 1994;Saravanane et al 1998;Choi et al 2002;Anupkumar et al 2005, Poornima et al 2005, 2006. These studies highlight the inhibition of microbial activities by anoxia and showed similarities in their distribution due to the homogenization of the watercolumn temperature profile in the mixing zone.…”
Section: Introductionmentioning
confidence: 91%
“…Thus, changes in environmental conditions transform the microbial activities, thereby conferring significant impact to the ecosystem (Choi et al 2002). In fact, marine bacteria's response to the addition of inhibitory substances, organic pollutants and heat has been studied elsewhere (Cole et al 1988;Hudak and Fuhrman 1988;White et al 1991;Shiah and Ducklow 1994;Saravanane et al 1998;Choi et al 2002;Anupkumar et al 2005, Poornima et al 2005, 2006. These studies highlight the inhibition of microbial activities by anoxia and showed similarities in their distribution due to the homogenization of the watercolumn temperature profile in the mixing zone.…”
Section: Introductionmentioning
confidence: 91%
“…Organic matter in surface waters is mineralized by planktonic and benthic bacteria, organisms whose activity is crucial for nutrient cycles and food webs [I]. Numerous studies have indicated that metabolic processes of microorganisms are very sensitive to pollutants [2,3] and hence the in situ activity of microbial communities has been used for establishing the effects of perturbations. The responses of aquatic bacteria to toxicants have been studied with various microbial techniques, including respiratory activity [4], acetate incorporation, glucosidase activity [ 5 ] , and, more recently, glucose metabolism [6], thymidine incorporation [7,8], and enzyme activity [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in microbial activities caused by changes in environmental conditions will thus confer significant impacts on functions of coastal ecosystems. In fact, marine bacterial responses to additions of inhibitory substances and organic pollutants have been extensively studied (Azam et al 1977, Siebers et al 1981, Hudak & Fuhrman 1988, Riemann & Lindgaard-Jørgensen 1990. Responses of marine bacteria and heterotrophic nanoflagellates (HNF) to temperature changes have also been studied in detail (Marrasé et al 1992, Shiah & Ducklow 1994.…”
Section: Introductionmentioning
confidence: 99%